Dinamika Asas Ultimum Remedium dalam Pemberantasan Tindak Pidana Korupsi di Indonesia dan Relevansinya dengan Prinsip Restorative Justice - Brian Kukuh Mediarto (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2024)
This study discusses the dynamics of the application of the principle of ultimum remedium in the eradication of corruption in Indonesia and its relevance to the principle of restorative justice. Corruption is seen as an extraordinary crime that requires a repressive approach and severe criminal sanctions, but on the other hand there is a discourse on the application of the principle of ultimum remedium which places criminal sanctions as the last step after other legal remedies are considered ineffective. This problem poses a dilemma in law enforcement, because it is faced with harsh demands for corruption eradication as well as efforts to realize more proportionate justice. This study uses normative juridical methods with legislative, conceptual, and case approaches, so that the analysis is focused on the applicable legal framework, criminal law theory, and application practices in the field. The results of the discussion show that the application of the principle of ultimum remedium in corruption crimes in Indonesia still raises debate, considering the characteristics of corruption that harm state finances and hinder development. On the one hand, this principle can be applied in a limited way to provide an alternative settlement space that places more emphasis on the recovery of state losses. On the other hand, its implementation is feared to weaken the deterrent effect and reduce public trust in the state's commitment to eradicating corruption. The relevance to the principle of restorative justice lies in the orientation of recovering state losses and fulfilling the sense of justice of the community, not solely the punishment of the perpetrator. Thus, this study emphasizes the importance of formulating policies that are balanced between repressive and restorative interests.